Dry Eye Syndrome in Non-Exophthalmic Graves' Disease. (2nd November 2015) - Bruscolini, A.; Abbouda, A.; Locuratolo, N.; Restivo, L.; Trimboli, P.; Romanelli, F.
ABSTRACT: Background : The present study aims to assess qualitative and quantitative characteristics of tear film and corneal related impairment and to evaluate the quality of life in a cohort of non-exophthalmic Graves' disease (GD) patients. Methods : The series comprised 50 eyes from 25 newly diagnosed GD patients with no proptosis. As control group, 56 eyes of 28 thyroid disease-free subjects were enrolled. Results : The results of Schirmer I and II, break-up time, and Oxford scheme showed a significant difference between GD and controls. By ocular surface disease index (OSDI) questionnaire, eleven (44%) GD patients had normal ocular surface, while two (8%) had mild, four (16%) had moderate, and eight (32%) had severe dry eye. The mean score of the OSDI in the GD group was significantly ( p  < 0.001) higher with respect to the control group. Conclusions : This study shows that the tear film and cornea are damaged in newly non-exophthalmic GD subjects.